Optimization of Batang Police Intelligence Raising in Countering Radicalism - Muchlas, Lazid Zaki (Indonesian Journal of Police Studies, 2024)
The use of social media on the internet in the current era of globalization makes the spread of information faster from one place to another. The speed of information causes many impacts in human life, both positive and negative impacts. The positive impact can be used to find out information in all parts of the world. However, on the other hand, there are negative impacts that can disrupt people’s lives. One example of the negative impact that exists is the development of radical understanding caused by the spread of deviant understanding with radical bases uploaded on social media. With this radical understanding, it will cause disruption to public security and order. Radical understanding can cause various disturbances in society such as actions that disrupt public facilities, demonstrations, unilateral actions carried out by radical groups, to acts of terrorism. Therefore, serious handling is needed from the police to eradicate radicalism. One of the functions that can play a role in counteracting radicalism is the intelligence unit. Intelligence units can carry out their duties both investigating, safeguarding, and raising radical organizations to maintain public security and order. Therefore, the author wants to discuss how the implementation of intelligence raising at the Batang Police Station and its optimization in counteracting radicalism. The problems raised in this writing are studied with the concept of optimization, the concept of mobilization, the concept of intelligence, the concept of radicalism, the theory of SWOT analysis, management theory and communication theory. This paper explains about the implementation of intelligence collection at the Batang Police Station which has not been optimal because it does not implement one of the principles in Perkabaintelkam, namely the principle of confidentiality / clandestine. Therefore, the author provides suggestions based on the Regulation of the Head of the Security Intelligence Agency Number 3 of 2013 concerning Intelligence Raising to the Batang Police Intelligence Satintelkam so that it is hoped that the existing suggestions can help optimize the raising carried out.